Factors Affecting Management of Epilepsy Amongest Epileptic Clients Receiving Services at Serere Health Centre IV Serere District. - Micheal Albert Olinga (Student's Journal of Health Research, 2021)
Background: Epilepsy is a neurological condition, which affects the nervous system. It is usually diagnosed after a person has had a least two sutures that were not caused by some known medical condition like; Alcohol withdrawal, extremely low blood sugar, heart problems, or some other medical condition. Epilepsy can also be diagnosed after a seizure if a patient has a condition that places them at risk for having another seizure. Methodology: The study had both quantitative and qualitative methods of data collection like; data collection tools. The data was collected from 30 respondents who were especially epileptic clients in the catchment area of the whole Centre. Data aggregation, entry, and analysis were done using the Micro-soft excel tool.  Results:   The study showed that the majority of the respondents were not married (66.7%), the majority of the respondents were below the age of 19 years (40%), also most of the respondents were not educated (40%), (10%) and (23.3%) blamed epilepsy on witchcraft and curse from God, (93.7%) have ever missed clinic day, (55%) had come alone to the clinic.  Recommendations: Therefore are that the concerned authority and well-wishers are called upon to take up the findings or conduct their study related to these problems to see the way forward.  In conclusion: Drug adherence, discrimination, low family social support, were the major factors affecting the management of epilepsy. These challenges would majorly be resolved through health education and counseling of the entire communities.